Kemampuan Servis Floating dan Jumping Peserta Ekstrakurikuler Bolavoli Putra MA NU Mazroatul Huda Karanganyar Demak 2022 (Universitas Negeri Semarang, 2022)
The problem that exists is that the ability of fluating and jumping services is not yet known which is currently widely used. This study aims to determine the fluating and jumping service abilities of the men's volleyball extracurricular members of MA NU Mazroatul Huda Karanganyar Demak This study uses a quantitative approach with a descriptive method. The variable of this research is the service on jumping and fluating. The population of this study was all participants in the men's extracurricular volleyball MA NU Mazroatul Huda Karanganyar Demak, totaling 15 participants. Using a saturated sampling technique to make a sample of all the existing population. The instrument used is the AAHPERD. The data were analyzed by descriptive percentage. The results showed that the fluating serve on the volleyball extracurricular participants Ma NU Mazroatul Huda Karanganyar Demak had an average value of 23,80 (50%). in the sufficient category. Meanwhile, the results of the jumping service had an average value of 15,73 (20%) in the sufficient category. The study's conclusion shows that the volleyball extracurricular participants' fluating serviceability is sufficient and the volleyball extracurricular participant's jumping serviceability is sufficient.